Premonitory sign of heart block in acute posterior myocardial infarction. Issue 1 (January 1975) - Barrillon, A; Chaignon, M; Guize, L; Gerbaux, A
Abstract : The appearance of the ARS complex in leads V3R and V4R was analysed in a series of 94 patients with acute posterior myocardial infarction. The cases of posterior myocardial infarction with direct signs of injury (ST segment elevation with a rise of 0.5 mm or more of point F and/or QS pattern) in leads V3R and/or V4R were complicated three times as often by atrioventricular block as those in which such signs were absent (66% and 22%, respectively; P smaller than 0.001). When one of these signs was present in leads V3R and/or V4R, the disorder of conduction was "severe" (complete atrioventricular block or sinotrial block with pauses) in half the cases and "unstable" (bradycardia below 50 beats/min; ventricular pause with or without syncope; widening of QRS complex; ventricular hyperexcitability) in one-third, justifying the introduction of a stimulating catheter. Such disorders were found, respectively, only 1 in 7 (14%), and less than 1 in 10 (8%) when these signs were absent (P smaller than 0.001). The association of ST segment elevation and QS pattern was rarer (15 cases) than the isolated finding of either sign. It was found in the most severe disorders of atrioventricular conduction. The changes observed in leads V3R and/or V4R before the appearance of atrioventricular block enable one to predict which patients with posterior myocardial infarction are the most likely to develop atrioventricular block. These electrocardiographic features seem to indicate septal involvement.